Prototyping Society Zur vorauseilenden Technologisierung der Zukunft - Dickel , Sascha (Science Studies, 2019)
Prototypes migrate from the workshops to society. They are no longer considered deficient because of incomplete objects. Rather, it is through the design of the material provisional that the social day after tomorrow is shaped and technologised. The production and reception of these artefacts is transformed from an exclusive expert activity to a public social practice: Prototypes are produced in publicly accessible Makerspaces and celebrated in urban event formats. Sascha Dickel shows that this can also be accompanied by a new form of criticism that does not oppose the technologization of the social, but opens up ways to design alternative futures in a technologically integrated world.